Factors influencing a secondary school physical education teacher's role as a pastoral head of year. (2nd October 2019) - Burrows, Adam; O'Leary, Nick
ABSTRACT: Utilising the occupational socialisation theoretical framework, this United Kingdom based case study explored how a secondary school physical education teacher fulfilled the head of year role and what childhood, university and on-the-job experiences influenced execution of this role. Data were collected from interviews, lesson observations and a self-reflective journal. Inductive data analysis and constant comparison identified that the participant attempted to be an 'administrative finisher' and 'empower' staff, parents and pupils. These aims were influenced by the de-prioritisation of physical education, a desire to retain control of administrative situations, and the influence of past and present teachers. To overcome the issues that the dual roles of head of year and subject teacher present, it is recommended that a 'timetabled' period at the beginning and/or end of the day be utilised for important head of year tasks, and greater formal responsibility is given to the assistant head of year. The findings of this study suggest further research possibilities. Firstly, there is a need to examine the influence of teaching other subjects whilst undertaking the head of year role. Secondly, investigating the impact of childhood and university socialisation upon teachers' fulfilment of other pastoral and/or leadership roles such as head of department, deputy head or head teacher appears warranted.